THE IMPORTANCE OF IMPROVING PHYSICAL FITNESS AND MOVEMENT OPPORTUNITIES OF YOUNG VOLLEYBALL ATHLETES - Abadan Ismailova (Web of Journals Publishing, 2023)
In this article, the role of physical qualities such as strength, quickness, endurance, agility, dexterity, flexibility and agility in the physical, technical and tactical training and general and special training of athletes in the sport of volleyball, and to what extent these physical qualities increase the level of the player's movement capabilities and has been discussed.
Keywords: Volleyball, sport, special training, technical training, tactical training, flexibility, athletes, agility, endurance.